Reimagining Goethe in the ELT Classroom: Divine Femininity and Islamic Traces in Faust and West-östlicher Divan - Candraningrum, Dewi; Setyabudi, Titis; Rahmayna, Kania Bening (Universitas Gadjah Mada, 2025)
This study explores the intersections of divine femininity and Islamic mysticism in Johann Wolfgang von Goethe’s Faust and West-östlicher Divan [West–Eastern Divan], positioning these canonical works as fertile ground for intercultural literary inquiry and postcolonial English Language Teaching (ELT). Employing hermeneutic, intertextual, and comparative literary methods, this research uncovers Goethe’s engagement with Sufi metaphysics, the Qur’an, and Persian poetic traditions—particularly his intertextual dialogue with Hafiz and the implicit spiritual kinship with Islamic thinkers such as Rabiah al-Adawiyah and Muhammad Iqbal. Central to this inquiry is Goethe’s concept of the Ewig-Weibliche [Eternal Feminine], which, when read through Islamic mystical lenses, reveals a syncretic spiritual vision that transcends Orientalist binaries and patriarchal norms. The paper argues that integrating these texts into ELT pedagogy encourages both aesthetic appreciation and critical intercultural understanding—especially within postcolonial, Muslim-majority contexts like Indonesia. By reinterpreting canonical Western literature through Islamic and gender-inclusive frameworks, this study contributes to both Goethean scholarship and transformative, decolonial approaches to literary pedagogy.